PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP PRESTASI BELAJAR ANAK (Kelas IV, V, VI) PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SDN 010 PULAU BUSUK JAYA KECAMATA INUMAN KABUPATEN KUANTAN SINGINGI - Peni Maya Rosa; Sarmidin Sarmidin; Helbi Akbar (AL-HIKMAH (Jurnal Pendidikan dan Pendidikan Agama Islam), 2020)
This study aims to determine the effect of Parental Education on Learning Achievement of Children (Class IV, V, VI) on Islamic Religious Education in SDN 010 Busuk Jaya Island Inuman District Kuantan Singingi District, the purpose of this study is to determine the Effect of Parental Education Level on Learning Achievement of Children (Class IV, V, VI) in Islamic Religious Education in SDN 010 Busuk Jaya Island Inuman District Kuantan singingi. This type of research is quantitative research. Data collection techniques using interviews / interviews, observation and documentation. The statistical method used is a simple linear technique regret. After calculating, the authors draw the conclusion that there is no significant effect between the influence of parents' educational levels on children's learning achievement (grades IV, V, VI) in Islamic religious education subjects at SDN 010 Busuk Jaya Island, Inuman District, Kuantan Singngi Regency ", Based on the hypothesis test, at a significance level of 5% obtained Fhit = 1.87 and Ft = 4.07; So Fhit <Ft means Freg is insignificant or rejected.